EVALUATION OF ANTIDIABETIC AND ANTIHYPERLIPIDEMIC EFFECT OF VERNONIA DIVERGENS IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - LAXMIDHAR MAHARANA; MANOJ KUMAR SETHI; RUDRA NARAYAN DASH; SNIGDHA PATTNAIK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current investigation for antidiabetic activity of the plant Vernonia divergens (DC.) Edgew. has not been reported till date. However, to enlighten the folkloric claim of the plant, the study was carried out on various animal models such as albino mice, albino rabbits, Wistar rats, rabbits, hamsters, dogs, and monkeys. Methods: The whole plant of V. divergens was studied on various animal models. Screening methods generally have been carried out on rodents and non-rodents, respectively. Various biochemical and hematological parameters such as serum glucose, plasma insulin, lipid profile and activities of liver enzymes, red blood cells, white blood cells, hemoglobin, and differential counts were measured to assess the antihyperglycemic and antihyperlipidemic activities as well as safety profile of the extract. Results: Among all experimental extracts of V. divergens, it was found that the aqueous and methanolic extracts had maximum control of blood glucose in diabetic Wistar rats. While comparing with normoglycemic animals, it was observed that reduction of blood sugar level and increase in plasma insulin level are maximum with test extract. Among the study, the effects of the methanolic extract of V. divergens (MEVD) and aqueous extract of V. divergens (AEVD) were done through oral route in both the models, i.e., normoglycemic and hyperglycemic animal models. The safety profile was evaluated by toxicological evaluation and observed that, even at a higher dose level of 3000 mg/kg body weight, the MEVD and AEVD were safe and retain normal physiological and behavioral effect. The whole protein, whole cholesterol, aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase enzyme activity of streptozotocin-administered rats showed significantly higher than normal rats, and the test extract-treated rats significantly reduced the elevated levels. Conclusion: It is concluded that the MEVD and AEVD (DC.) Edgew. might be beneficial in effectively reducing the blood glucose concentration and managing the various complications of diabetes. However, in comparison between both the extracts, the methanol extract was found to be significantly more potent than that of the A.E. in all aspects.